The Use Of PBL-Based Interactive Multimedia To Develop Student Science Process Skill - Fitriani, W.; Abdulah, Abdulah; Mustadi, A. (Universitas Pendidikan Ganesha, 2021)
Natural science was a lesson content that equipped and prepared students to have various essential skills for life; one of them is science process skill. However, natural science learning used for investing this skill was not run maximally, proven from the process and learning outcome. This research aimed to offer a solution related to that problem by developing Problem Based Learning-based interactive multimedia and effectiveness testing of PBL-based interactive multimedia to improve the science process skill. The research approach was research and development in which the research subjects consisted of students and teachers from cluster 01, Depok Sub-district, Sleman. The first field test obtained a score of 3.2, which was included in a mediate category, while the operational field test obtained a score of 4.3, which was included in the very good category. The independent t-test obtained a significance of 0.001 <0.05, meaning that there was a significant difference between the experimental and control classes. This research was implied that the learning media and model could influence the achievement of the student. Therefore, the selection should be well considered according to the learning characteristics and students.